2021
DOI: 10.26710/jafee.v7i1.1589
|View full text |Cite
|
Sign up to set email alerts
|

Disintegrated Market Orientation and Firm Performance: Moderating Effect of Entrepreneurial Orientation

Abstract: The interplay between strategic orientations has received limited attention in manufacturing small and medium enterprises (SMEs).The existing studies have repeatedly called for investigating the impacts of multiple strategic orientations on organizational performance. Moreover, prior research called for disintegrating the strategic orientation and assessing their effects on organizational performance. Thus, this study is the first of its nature – disintegrating the market orientation (MO) construct and using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…The Innovativeness of SMEs is one of the essential components of the growth of small businesses (Mkalama, B., Ndemo, B., Maalu, J., & Pokhariyal, G., 2021). A survey to unravel the interplay of strategic orientations in improving the performances of manufacturing small businesses found that entrepreneurial orientation enhances market orientation's significant positive impact on SMEs' performances (Hussain, J., Bibi, P., Ahmad, A., & Bilal, H., 2021). A study revealed that entrepreneurial orientation does not influence the performance of the firms but suggested that when a firm introduces innovation into its products, it influences performance (Hendayana, 2021).…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%
“…The Innovativeness of SMEs is one of the essential components of the growth of small businesses (Mkalama, B., Ndemo, B., Maalu, J., & Pokhariyal, G., 2021). A survey to unravel the interplay of strategic orientations in improving the performances of manufacturing small businesses found that entrepreneurial orientation enhances market orientation's significant positive impact on SMEs' performances (Hussain, J., Bibi, P., Ahmad, A., & Bilal, H., 2021). A study revealed that entrepreneurial orientation does not influence the performance of the firms but suggested that when a firm introduces innovation into its products, it influences performance (Hendayana, 2021).…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%